Un-silencing youth trauma : transformative school-based strategies for students exposed to violence & adversity - Garo, Laurie A.; Butler, Bettie Ray, 1981-; Lewis, Chance W. 1972- (Contemporary perspectives on access, equity, and achievement., 2022)
"Urban violence, poverty, and racial injustice are ongoing sources of traumatic stress that affect the physical, emotional and cognitive development and well-being of millions of children each year. Growing attention is therefore directed toward the study of child trauma and incorporation of trauma-sensitive practices within schools. Currently such practices focus on social and emotional learning for all children, with some in-school therapeutic approaches, and outside referrals for serious trauma. There is inadequate attention to racial injustice as an adverse childhood experience (ACE) confronting Black males among other youth of color. Although there are guidelines for trauma-sensitive approaches, few are culturally responsive. And it is now critical that educators consider the traumatic impacts of a dual pandemic (covid-19 and racism) on children and their education. This timely book thus serves to inform and inspire transformative healing and empowerment among traumatized children and youth in pandemic/post-pandemic school and after-school settings. The reader will learn about trauma through actual experiences. Researchers and practitioners present approaches to healing that can be adapted to local situations and settings. The book consists of four parts: Youth Voices on Traumatic Experience; Trauma-focused Research; Culturally Responsive and Trauma Sensitive Practices; and Where do we go from Here? Suggestions for Next Steps. Each part contains a set of themed chapters and closes with a youth-authored poetic expression. The book is especially designed for those working in urban education. However, anyone whose work is related to traumatized children and youth will find the book informative, especially in a post-pandemic educational environment"--